Encountering Berlant part one: Concepts otherwise. Issue 1 (25th December 2022) - Anderson, Ben; Aitken, Stuart; Bacevic, Jana; Callard, Felicity; Chung, Kwang Dae (Mitsy); Coleman, Kathryn S.; Hayden, Robert F.; Healy, Sarah; Irwin, Rita L.; Jellis, Thomas; Jukes, Joe; Khan, Salman; et al.
Abstract: In Part 1 of 'Encountering Berlant', we encounter the promise and provocation of Lauren Berlant's work. In 1000‐word contributions, geographers and others stay with what Berlant's thought offers contemporary human geography. They amplify an encounter with their work, demonstrating how a concept, idea, or style disrupts something, opens up a new possibility, or simply invites thinking otherwise. The encounters range across the incredible body of work Berlant left us with, from the 'national sentimentality' trilogy through to recent work on negativity. Varying in form and tone, the encounters exemplify and enact the inexhaustible plenitude of Berlant's thought: fantasy, the case, love, impasse, feel tanks, slow death, ellipses, gesture, attrition, intimate public, ambivalence, style. Part 2 of 'Encountering Berlant' focuses on Berlant's most influential concept: 'cruel optimism'. Across these heterogeneous encounters, Berlant's enduring concern with the tensions and possibilities of relationality and how to enact better forms of common life shine through. These enduring concerns and Berlant's commitment to the incoherence and overdetermination of phenomena are summarised in the Introduction, which also explores how Berlant's work has been engaged with in geography. The result is a repository of what an encounter with Berlant's thought makes possible. Short Abstract: Part 1 of 'Encountering Berlant' explores the promise and provocation of Lauren Berlant's work. Contributors amplify an encounter with Berlant's concepts, tones, and styles, drawing out their implications for understanding relationality and how to invent and live better ways of being in common. The result is a repository of what Berlant's thinking offers geographers.